Pattern of ENT- Head and Neck Diseases in Outpatient Department in a District Level Hospital in Bangladesh - Mahfuz, Md Sirazul Islam; Kabir, Ahmed; Sharif, Ahmed (Bangladesh Journal of Otorhinolaryngology, 2020)
Aims: To determine the pattern of Otorhinolaryngology- Head and Neck diseases in Gopalganj and neighbouring districts. Methods: This was a prospective cross sectional study which was carried out patients of ENT- Head & Neck diseases attendant in 250 Bedded General Hospital, Gopalganj. A total 8700 patients were attendant in OPD during period of July 2015 to June 2016. Result: In this study 45.55% were male & 54.45% female. Male female ratio 1:1.2. Age ranges from 0 to 90 years, mean age of patients 44.522 years(SD 26.16), majority of patients were age group 0 to 15 (39.10%). Top most ten diseases were chronic tonsillitis (9.50%), adenoid hypertrophy (9%), acute otitis media(7.70%),chronic otitis media(7.59%), rhinitis(7.16%), acute tonsillitis(6.50%), wax(6.40%), hearing loss & tinnitus(5.70%), rhinosinusitis (3.24%), deviated nasal septum (2.80%). Conclusion: The findings help defining the content and extent of medical curriculum in otorhinolaryngology, there by enriching the local medical graduates in their pursuit of relevant knowledge and skill in managing the relatively common and prevailing ENT diseases in Bangladesh. Therefore, there is a need for increased awareness of the people in developing countries especially in Bangladesh through social campaigns and health education aimed at providing quality ear, nose, and throat health care services. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 74-82